2018
DOI: 10.1590/2179-8087.021415
|View full text |Cite
|
Sign up to set email alerts
|

Performance of tamboril Seedlings Produced in Three Different Tube Volumes

Abstract: The objective of this study was to evaluate the performance of tamboril (Enterolobium contortisiliquum (Vell.) Morong) seedlings and define their time in the nursery. Two experiments were carried out; in the first, the seedlings remained in the nursery for 120 days, and height, diameter, root deformation %, shoot dry mass, root system and leaf number were evaluated. In the second experiment, four seedlings of each repetition were transplanted into 35 x 40 cm bags and then assessed for height, diameter and dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
8
Order By: Relevance
“…De acordo com Freitas et al (2018), na produção de mudas florestais, o tempo de permanência dessas no viveiro é um dos maiores problemas enfrentados, para que não seja prejudicada a sobrevivência e crescimento pós-plantio.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…De acordo com Freitas et al (2018), na produção de mudas florestais, o tempo de permanência dessas no viveiro é um dos maiores problemas enfrentados, para que não seja prejudicada a sobrevivência e crescimento pós-plantio.…”
Section: Introductionunclassified
“…Cruz, Andrade e Feitosa (2016) recomendaram o uso de recipiente de menor volume para produção de mudas de Spondias tuberosa em função dos gastos com substrato. Freitas et al (2018) observaram para Enterolobium contortisiliquum (Vell.) Morong que recipientes de 180 e 280 cm³ apresentaram similaridade em qualidade das mudas, recomendando o uso do recipiente de 180 cm³ para um ciclo de produção de 90 dias.…”
Section: Introductionunclassified
“…This study agrees with those of Lisboa et al (2012) when working with Australian cedar, who identified tubes with a volumetric capacity of 288 cm 3 as the best containers to produce seedlings of these species. Moreover, Freitas et al (2018) found that tamboril seedlings produced, among others, with tubes of the same dimensions, showed promising results.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of plastic bags is the low acquisition cost compared to tubes. Despite this, the tubes are reusable and have advantages such as occupying a smaller area in the nursery, reducing labor, greater practicality in planting, and greater practicality due to easy handling (CORREIA et al, 2013, FREITAS et al 2018. Therefore, using tubes leads to higher planting yields, which can reduce the costs of this operation and favor mechanized planting.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main factors, the type of container and its dimensions highly influence forest species seedling quality and production costs, being significant for plant growth (Pias et al 2015). A suitable container must ensure the proper development of the root system until the seedling dispatch stage, generating good architecture and aggregating roots to the substrate, and thus favoring the survival and initial growth of seedlings in the field (Freitas et al 2018).…”
Section: Introductionmentioning
confidence: 99%